2019
DOI: 10.1001/jamasurg.2019.3019
|View full text |Cite
|
Sign up to set email alerts
|

Defining Value for Pancreatic Surgery in Early-Stage Pancreatic Cancer

Abstract: IMPORTANCE Value-based care is increasingly important, with rising health care costs and advances in cancer treatment leading to greater survival for patients with cancer. Regionalization of surgical care for pancreatic cancer has been extensively studied as a strategy to improve perioperative outcomes, but investigation of long-term outcomes relative to health care costs (ie, value) is lacking. OBJECTIVE To identify patient and hospital characteristics associated with improved overall survival, decreased cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…48 Similarly, a retrospective study using the CCR found no differences by race, ethnicity, or SES in survival following resection for stages I/II pancreatic cancer after controlling for age, sex, comorbidity, tumor stage and grade, type of surgery, chemotherapy, and surgical volume of the hospital. 49…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 Similarly, a retrospective study using the CCR found no differences by race, ethnicity, or SES in survival following resection for stages I/II pancreatic cancer after controlling for age, sex, comorbidity, tumor stage and grade, type of surgery, chemotherapy, and surgical volume of the hospital. 49…”
Section: Resultsmentioning
confidence: 99%
“…22 The finding of comparable outcomes following surgery (when controlling for surgical volume) may extend to some regions. 49…”
Section: Resultsmentioning
confidence: 99%
“…Surgical volume and expertise have an impact on both clinical and oncologic outcomes in patients treated for borderline resectable and resectable PC . Few centers with an annual volume of more than 20 MIPS procedures for PC have published their outcomes, and available data are too heterogenous to allow comparative analysis .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical volume and expertise have an impact on both clinical and oncologic outcomes in patients treated for borderline resectable and resectable PC. 24 Few centers with an annual volume of more than 20 MIPS procedures for PC have published their outcomes, and available data are too heterogenous to allow comparative analysis. 25 After pancreatic surgery, the absolute differences in adjusted mortality between the lowest and highest volume hospitals were found to be among the highest.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Pancreatic cancer, a notoriously aggressive disease with complex management, has in recent years been aggregated to specialized medical centers. In this issue of JAMA Surgery , Bateni et al present a review of outcomes and cost after attempted curative resection for early-stage pancreatic adenocarcinoma. Data were obtained from the California Cancer Registry along with the Office of Statewide Hospital Planning and Development.…”
mentioning
confidence: 99%